Isolation and Characterization of Antimicrobial Constituent(s) from the Stem of Cissus populnea Guill. & Perr. - Anita Alex-Asaolu; Ahmad Uba; Umar Abubakar Birnin-Yauri; Amina Jega Yusuf (Drugs and Drug Candidates, 2024)
Cissus populnea Guill. & Perr. (Vitaceae) is used in traditional medicine to treat microbial infections, venereal diseases and infertility, among others. The aim of this research is to isolate and characterize the antimicrobial constituent(s) from the stem of C. populnea. The n-butanol fraction of C. populnea, being most active, was subjected to silica gel column chromatography, which led to the isolation of white solid and white crystalline substances coded compounds C1 and C4C5, respectively. Spectral analysis (1D and 2D-NMR) of the isolated compounds and comparison with the literature data indicated C1 to be Bis-(2-ethyloctyl)-phthalate and C4C5 to be a mixture of stigmasterol and β-sitosterol; C4C5 exhibited a zone of inhibition ranging from 24 to 29 mm against the test organisms with Candida albicans being the most sensitive organism while Trichophyton rubrum was the least sensitive organism. Of the standard drugs, ciprofloxacin had 27–37 mm while fluconazole and fulcin exhibited zones of inhibition ranging from 34 mm to 29–32 mm, respectively. The MIC and MBC/MFC values for C4C5 ranges from 12.5 to 25.0 µg/cm3 and 25.0 to 50.0 µg/cm3 against methicillin-resistant Staphylococcus aureus, Staphylococcus. aureus, Escherichia coli, Candida albicans, Trichophyton rubrum and Trichophyton mentagrophyte, respectively. In conclusion, Bis-(-(2-ethyloctyl)-phthalate) and a mixture of stigmasterol and β-sitosterol were identified for the first time from the stem of C. populnea.